Graphene: Thiofluorographene–Hydrophilic Graphene Derivative with Semiconducting and Genosensing Properties (Adv. Mater. 14/2015). (April 2015) - Urbanová, Veronika; Holá, Kateřina; Bourlinos, Athanasios B.; Čépe, Klára; Ambrosi, Adriano; Loo, Adeline Huiling; Pumera, Martin; Karlický, František; Otyepka, Michal; Zbořil, Radek
<x xml:space="preserve">Abstract</x> Thiofluorographene, a new derivative of graphene, is prepared by R. Zbořil and co‐workers on page 2305. Through nucleophilic substitution of fluorine atoms by ‐SH groups in a polar solvent, the first example of covalent chemistry on fluorographene is presented. The resulting two‐dimensional material is hydrophilic with semiconducting and genosensing properties as demonstrated by DNA sensing using electrochemical impedance spectroscopy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>